PENGARUH PENGGUNAAN KARTU HURUF TERHADAP KEMAMPUAN MEMBACA SISWA SD KELAS IV - Nabila, Nabila; Apdoludin (Program Studi Pendidikan Vokasi Seni Kuliner, 2026)
This study aims to determine the effect of using letter cards on the reading ability of fourth-grade students at SDN 90/II Talang Pantai. The issue addressed is the students’ low reading ability, indicated by their difficulty in recognizing letters and forming words. The research subjects consisted of 10 fourth-grade students who had reading difficulties. This research employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. The results showed a significant improvement in students’ reading ability after using letter cards. The average reading score increased from the pretest to the posttest. Thus, letter cards are proven to be effective in enhancing elementary school students' reading skills.